Autoimmune Primary Adrenal Insufficiency in Children - Nádia Mourinho Bala; Raquel S. Gonçalves; Joana Serra Caetano; Rita Cardoso; Isabel Dinis; Alice Mirante (Galenos Yayincilik, 2022)
INTRODUCTION: Primary adrenal insufficiency (PAI) is a rare condition in children, and is potentially life-threatening. The most common cause is congenital adrenal hyperplasia, and autoimmune etiology is the most frequent acquired cause in this age group. Symptoms are usually non-specific and, when suspected, investigation should include adrenocorticotropin hormone (ACTH) and morning serum cortisol measurement and, in some cases, a cosyntropin test to confirm the diagnosis. Prompt treatment is essential to prevent an adverse outcome. METHODS: We retrospectively collected clinical and laboratory data from adrenal insufficiency due to autoimmune adrenalitis, observed from 2015 to 2020 in a pediatric endocrinology department of a tertiary care hospital. RESULTS: Eight patients were identified, seven males and one female, with age at diagnosis between 14 and 17 years. The symptoms at presentation ranged from non-specific symptoms, such as chronic fatigue and weight loss, to a severe presentation, with altered mental status and seizures. The median duration of symptoms was 4.5 months. The diagnosis was confirmed by serum cortisol and plasma ACTH measurement and all were confirmed to have autoimmune etiology (positive anti-adrenal antibodies). At diagnosis, the most common laboratory abnormality was hyponatremia. All patients were treated with hydrocortisone and fludrocortisone. One patient presented with evidence of type 2 autoimmune polyglandular syndrome. DISCUSSION AND CONCLUSION: PAI is a rare condition in the pediatric age group. Due to non-specific symptoms, a high index of suspicion is necessary to establish a prompt diagnosis. Once an autoimmune etiology is confirmed, it is important to initiate the appropriate treatment and search for signs and symptoms of other autoimmune diseases during follow-up.